Mapping the needs and challenges of SMEs: A focus on the city of Johannesburg entrepreneurship ecosystem - Jabulile Msimango-Galawe; Buntu Majaja (Cogent Business & Management, 2022)
Entrepreneurship ecosystems have increased in popularity to foster more entrepreneurial activity and, hence, spurring economic growth and employment creation. To explore the state of the City of Johannesburg’s entrepreneurship ecosystem and identify the gaps and weaknesses that cause the ecosystem not to function optimally. This is through the lens of the challenges and needs of entrepreneurs in the city This research was a propagation of this phenomenon within the context of Africa and focusing more specifically on the City of Johannesburg in South Africa. This was a cross-sectional, quantitative study with a sample of 1099 entrepreneurs. Data analysis included aggregating and analysing the data through descriptive statistics, simple observation, comparison, and pattern recognition. The study’s findings showed a map of the City of Johannesburg’s entrepreneurship ecosystem’s issues and how entrepreneurs across different regions are not affected differently by the geographic region. The key challenges were access to markets, equipment, and suppliers, and the critical needs identified were investors, suppliers, and entrepreneurship education. After mapping the challenges and needs of entrepreneurs to the ecosystem framework, it was evident that the three entrepreneurship ecosystem domains which represent the most significant barrier for entrepreneurs in the City of Johannesburg were access to markets, finance, and human capital. It is also found that the spatial divide effect in the city lowers access to markets for entrepreneurs. The study recommends that COJ need to support entrepreneurs in a more structured way taking an integrated approach, so support is not fragmented as it is evident that all is linked within the ecosystem and they all affect each other in tandem, i.e. access to markets, finance and human capital.